(untitled) (Scientific journal of the Fergana State University, 2024)
Today, studying and researching the works of writers who have made a significant contribution to modern Uzbek prose is one of the most urgent issues. Current Uzbek literature, in particular, the artistry in the work, nationalism is considered one of the main issues. Nationalism reflects the ideological and artistic views of the writer. The artist, as a representative of a people, reflects the elements of nationalism characteristic of his mentality in his works. Through the character, external structure, and way of life of the characters, the creator shows the national characteristics typical of the representatives of the people to which he belongs. In this article, the issue of nationality in the artistic work, the place of the national color in the artistic work, the details and traditions specific to the national mentality were studied. The story "Enashamol" by the talented writer Bahadir Qabul was researched. It was determined that the originality of the writer’s work, the elements of nationality are presented in a unique way. In the short story "Enashamol", the author shows the national ideology through artistic details and traditions.